ANALYSIS OF THE ROAD CAPACITY AND GENERATED PARKING IN THE SHOPPING CENTER BLAURAN MARKET PALANGKARAYA CITY - Lola Cassiophea (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2015)
Imbalances between the number of parking vehicles and off-street parking facilities resulted in parking generation to automatically take the off-street area. Based on analysis on road capacity in the Blawuran traditional market segment on Jl. Ahmad Yani, it is known that the service level still meet as Transportation Ministry No. KM14 of 2006, AASTHO 1973 and Morlok 1990. Value of capacity service availability on Jl. Ahmad Yani on Tuesday morning is free flow and Tuesday afternoon is steady stream. However, on Saturday night, the road section is near to unstable flow. On Tuesday morning, traffic density is low with medium to high velocity but could be controlled by driver according to speed maximum/minimum limits and physical road conditions. On Tuesday noon, traffic density is medium with high speed but still could be controlled by driver according to speed maximum/minimum limit and physical road contion as well. However, on Saturday night, the traffic density is so high with low speed as consequences even still controlled by driver. Total hourly parking vehicles is 15 vehicles/hour. This value is adjusted to supplied vehicles in and out of market which is 139 vehicles/hour. Therefore, parking availability is still adequate to accomodate vehicles in Blawuran traditional market.